2017
DOI: 10.3917/assy.111.0109
|View full text |Cite
|
Sign up to set email alerts
|

Two Pazuzu-head amulets inscribed with the standard B incantation

Abstract: L’article porte sur deux amulettes inscrites représentant la tête de Pazuzu. La première est une pièce en bronze inédite provenant de la collection de Charles-Louis-Marie de l’Écluse, conservée à la Bibliothèque Nationale de France depuis 1906. La seconde, acquise à Bagdad et donnée au Musée du Louvre par G. Maspero en 1883, fut publiée par le Père J.-V. Scheil en 1894. Toutes deux portent différentes versions de l’incantation standard B, nommée “Die akkadische Beschwörung” par R. Borger. La présente étude ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…This creature needed to have combined in itself both the features of familiar apotropaion, similar to Huwawa, and those of a restless passenger to and from the liminal zones (Wiggermann 2007, 135). 9 From the fact that clay heads of Pazuzu were mass produced for a wide-spread consumption, it can be concluded that, according to the belief, Pazuzu's power was identified mostly with the head and the face. It is the most prominent essential feature of this demon.…”
Section: The Ambivalent Pazuzumentioning
confidence: 99%
“…This creature needed to have combined in itself both the features of familiar apotropaion, similar to Huwawa, and those of a restless passenger to and from the liminal zones (Wiggermann 2007, 135). 9 From the fact that clay heads of Pazuzu were mass produced for a wide-spread consumption, it can be concluded that, according to the belief, Pazuzu's power was identified mostly with the head and the face. It is the most prominent essential feature of this demon.…”
Section: The Ambivalent Pazuzumentioning
confidence: 99%
“…Иако не е лекар, таа сепак става завои; иако не е бабица, таа сепак го брише и чисти новороденчето; ги брои месеците на бремените жени, постојано блокирајќи ги вратите на жените кои треба да се породат. Ламашту го грабнува момчето при молитва, девојката при игра, детенцето од рамото на дадилката (OB3, [3][4][5][6][7][8][9][10][11]. било кој нема божествена заштита.…”
unclassified